Age‐dependent release of high‐mobility group box protein‐1 and cellular neuroinflammation after traumatic brain injury in mice. Issue 6 (30th December 2018) - Webster, Kyria M.; Sun, Mujun; Crack, Peter J.; O'Brien, Terence J.; Shultz, Sandy R.; Semple, Bridgette D.
Abstract: Accumulating research suggests that children may be more vulnerable to poor long‐term outcomes after traumatic brain injury (TBI) compared to adults. The neuroinflammatory response, known to contribute to neuropathology after TBI, appears to differ depending upon age‐at‐insult, although this response has not been well‐characterized. Elevated levels of a key initiator of inflammation, high‐mobility group box protein 1 (HMGB1), have been associated with worsened outcomes after TBI in young patients. This study therefore aimed to characterize the acute time course of key mediators of the inflammatory cascade, including HMGB1, after pediatric and adult TBI. Male C57Bl/6 mice were subjected to severe controlled cortical impact or a sham control surgery, at either early adulthood (8–10 weeks) or a pediatric age (3 weeks). Cortical tissue was collected for Western blot detection of astrocyte and microglial activation (GFAP and CD68) and HMGB1 at 2 hr, 6 hr, 24 hr, 3 days, and 7 days postinjury, and serum was collected for enzyme‐linked immunoassays to quantify peripheral HMGB1. An additional cohort of brains was harvested at 3 day postinjury for immunofluorescence staining. Results demonstrated a temporal profile of CD68, GFAP, and HMGB1 after TBI relative to sham, which differed between the adult and pediatric cohorts. An increase in peripheral HMGB1 was found in serum from pediatric TBI mice, which was not evident in adult serum. Together, these findings demonstrate that HMGB1 and the downstream cellular inflammatory response are influenced by age‐at‐insult, which may be an important consideration for treatment strategies aiming to ameliorate this response after TBI. Abstract : Traumatic brain injury (TBI) triggers a neuroinflammatory response including activation of astrocytes and reactive microglia, alongside neuronal loss. These cells can release high‐mobility group box protein‐1 (HMGB1). These processes are influenced in both magnitude and temporal nature by the age‐at‐injury.